Pengetahuan dalam Penggunaan Sistem Pencegahan Kebakaran dalam Kalangan Penghuni Bangunan Kediaman Bertingkat - Rosdi, Mohammad Amin; Sarpin, Norliana; Kai Chen, Goh; Shafii, Haryati (Research in Management of Technology and Business, 2022)
Fire incidents are often considered to be accidents that are difficult to contain. There are several causes of fire incidents in multi-storey buildings, among others due to the lack of knowledge regarding the use of fire prevention systems among residents and they also take safety issues lightly. Therefore, the objective of this study is to identify the factors of fire in multi-storey residential buildings, identify the type of knowledge required by residents about fire prevention equipment and suggest measures that can be taken to improve the knowledge of residents of multi-storey residential buildings in the use of fire prevention equipment. The scope of this study involves residents in the Bukit Beruntung area in Selangor. The research instrument used was the questionnaires survey with 195 residents of multi-storey residential buildings. Meanwhile, the data analysis technique used is descriptive analysis using Statistical Package for Social Sciences (SPSS) software. The results of the study found that the main factors in the occurrence of fire are fire prevention equipment such as hose coils and fire extinguishers that are not well maintained and cannot be used. The study also found that the main type of important knowledge regarding fire prevention system is that every resident of a multi-storey residential building needs to know the position of fire prevention equipment such as hose coils and fire extinguishers. Finally, a key measure to increase building resident knowledge is to ensure that every resident knows the importance of having fire prevention equipment such as hose coils and fire extinguishers and increase knowledge related to the operation of fire prevention equipment by giving practical training to the resident. In conclusion, knowledge of fire prevention system tools is very important to prevent fires in multi -storey residential buildings and can save lives and property.